Coronary Artery Fistula Diagnosed by Echocardiography during NSTEMI: Case Report and Review of Literature. (14th August 2019) - Acitelli, Angelo; Bencivenga, Sabrina; Giannico, Maria B.; Lanzillo, Chiara; Maresca, Luciano; Petroni, Renata; Penco, Maria; Calò, Leonardo; Romano, Silvio
Abstract : Coronary artery fistulas are rare abnormal connections between a coronary artery and a cardiac chamber or a major vessel. Often, they are asymptomatic and the diagnosis is accidental. The case we present is the incidental finding of a fistula displayed with echocardiography during acute coronary syndrome (ACS). A 73-year-old man presented in the emergency room for non-ST-elevation ACS. Echocardiogram showed in a parasternal short axis view an abnormal diastolic flow inside the ventricular inferior wall. Angiography and CT confirmed the diagnosis of coronary fistula from the right coronary into the left ventricular cavity. A literature analysis with discussion about coronary fistulas classification and management was also performed.